2006
DOI: 10.1128/jvi.80.6.2718-2727.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Four Proteins Encoded by the Human Cytomegalovirus UL112-113 Region Regulate Their Intranuclear Targeting and the Recruitment of UL44 to Prereplication Foci

Abstract: Four phosphoproteins, of 34, 43, 50, and 84 kDa, with common amino termini are synthesized via alternative splicing from the UL112-113 region of the human cytomegalovirus genome. Although genetic studies provided evidence that both the UL112 and UL113 loci in the viral genome are required for efficient viral replication, whether the four proteins play specific roles or cooperate in replication is not understood. Here we present evidence, using in vitro and in vivo coimmunoprecipitation assays, that the four UL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…It is highly homologous in its structure to the UL112-113 region of human cytomegalovirus (16,47,60). Although the mechanisms of action of the E1 proteins have not been fully elucidated, a number of studies have shown that they play an important role in the formation of nuclear replication compartments (4,38,40), in viral DNA replication (37,61), and in the regulation of gene expression (24,28,49). Hence, we thought that the mutations in M112/M113 might play a role in the ability of MCMV/h to replicate in human cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is highly homologous in its structure to the UL112-113 region of human cytomegalovirus (16,47,60). Although the mechanisms of action of the E1 proteins have not been fully elucidated, a number of studies have shown that they play an important role in the formation of nuclear replication compartments (4,38,40), in viral DNA replication (37,61), and in the regulation of gene expression (24,28,49). Hence, we thought that the mutations in M112/M113 might play a role in the ability of MCMV/h to replicate in human cells.…”
Section: Resultsmentioning
confidence: 99%
“…At the early stages of infection, UL112-113 proteins appear in nuclear domain 10 (ND10) (Ahn et al, 1999;Penfold & Mocarski, 1997). UL112-113 proteins act as pre-replication factors that seed the replication complex by sequentially recruiting single-stranded DNA-binding protein (pUL57) and DNA polymerase processivity factor (pUL44) to ND10 (Park et al, 2006;Penfold & Mocarski, 1997). Furthermore, this observation is strengthened by the fact that UL112-113 interacts with UL44 (Iwayama et al, 1994; Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The M112-113 gene consists of three exons, and alternative splicing creates at least 4 proteins (33,36,38, and 87 kDa) (8,10). UL112-113 is 1 of the 11 core proteins that are essential for HCMV DNA replication (11,12), and it interacts with the lytic origin of replication (13) and forms prereplication domains by recruiting a diversity of viral and cellular proteins that are important for DNA replication (14,15).…”
mentioning
confidence: 99%